Changes of spleen dendritic cells in the terminal stage of multipleorgan dysfunction syndrome - Jiangyang, L.; Quian, L.; Xiaohong, W.; Yi, Y. (Acta Biomedica Atenei Parmensis, 2011)
Immune dysfunction is associated with the onset of multiple organ dysfunction syndrome (MODS). To study the immune damage in the spleen, we observed pathological features of the spleen and investigated the number of splenic dendritic cells and T lymphocytes in MODS patients, 9 human MODS cases and 25 normal spleens were examined by light microscope, electron microscope and immunohistochemistry (S-100, CD11c, CD205, CD1a, CD80 and HLA-DR). There was resolution and dispersion of splenic corpuscles, especially white corpuscles, accompanied by apoptosis of a large amount of lymphocytes and increased number of splenic dendritic cells (DCs). CD1a+/S-100+ DCs and CD205+/S-100+ DCs increased but the CD80+/CD11c+ DCs and CD1a+/HLA-DR+DCs decreased in MODS patients(p